Influence of light ion irradiation of the oxide layer on the oxidation rate of Zircaloy-4. (September 2015) - Verlet, Romain; Tupin, Marc; Baldacchino, Gérard; Wolski, Krzysztof; Miro, Sandrine; Gosset, Dominique; Colas, Kimberly; Jublot, Michael; Jomard, François
Highlights: The appearance of two new vibration bands on RAMAN spectra linked to irradiation defects. 18 O flux increase with ion fluence. The existence of a link between the intensities of the two new RAMAN bands and the flux of 18 O. The kinetic acceleration after irradiation lasts up to 23 days in PWR simulated conditions. Abstract: A strong increase of the oxidation rate of Zircaloy-4 fuel cladding is observed for burnups above 35 GWd/MtU in PWR. This kinetic acceleration could be in large part due to the irradiation damage. To quantify the effect of the oxide layer irradiation on the Zircaloy-4 corrosion rate, a new approach was used. Defects created by light ion irradiation increase the oxidation rate of the alloy up to 23 days in autoclave in agreement with the irradiation defect annealing characterized by RAMAN spectroscopy. A simple model taking into account the annealing of the irradiation defect is proposed to explain the results.